Mastery versus profit as motivation for the entrepreneur: How crony policies shape business. Issue 1 (11th April 2016) - Manish, G.P.; Sutter, Daniel
Abstract : Purpose: – The purpose of this paper is to argue that entrepreneurs are motivated not only by the desire to maximize profits but also by the desire for mastery. It then attempts to analyze the implications of mastery seeking for the economics and politics of government privileges and favors for businesses. Design/methodology/approach: – Using the existing psychological literature on mastery as motivation the paper first attempts to conceptualize how the desire for mastery manifests itself in the context of entrepreneurship. Next, it attempts to clarify the implications of this for the existing literature on the effects of government policies promoting cronyism. Findings: – The paper argues that in business mastery involves producing a good product or service, and validation of the performance occurs via the choices of sovereign consumers. Mastery is thus achieved through participation in a process of competition that is free from government favors. Given that crony polices can disrupt the consumer choice process and consequently the validation of performance, they can therefore affect the types of individuals who become entrepreneurs, with a high level of government intervention pushing success seekers to pursue mastery in other life endeavors, with adverse implications for innovation and growth in the economy. Originality/value: – The exploration of implications of a plausible but underexplored motive for entrepreneurs and the interaction between this motive and the effects of various policies fostering cronyism or rent seeking are potential contributions of the paper.